Infusion of Environment Dimension of ESD into Science Learning Through the RADEC Learning Model in Elementary Schools - Hana Lestari; Muhammad Ali; Wahyu Sopandi; Ana Ratna Wulan (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to provide an overview of infusion of environment dimension of ESD into thematic learning thought the RADEC learning model in elementary schools. This study used a descriptive qualitative approach involving four teachers and twenty students in elementary school Bogor City who were taken based on purposive sampling technique. Data were collected through interviews, observation, and primary school science curriculum documents, which were processed using triangulation techniques. The results of this study indicate that in general, indicators derived from basic competencies can be oriented towards the goal of sustainable education in the dimensions of environmental preservation. Natural science learning which is packaged in thematic learning at the elementary school level can provide opportunities in the process of implementing sustainable development education holistically and comprehensively. The RADEC model can stimulate students to learn actively, not only mastering the concept of environmental conservation but also thinking skills and attitudes in preserving the environment. The RADEC model can be applied in synchronous and asynchronous online learning so it is suitable for use during the Covid-19 pandemic